The Implementation of Inclusive Curriculum in Al Azhaar Islamic Elementary School and Noble National Academy Elementary School in Creating Children-Friendly School - Nita Agustina Nurlaila Eka Erfiana; Imam Fuadi; Agus Zaenul Fitri; Ngainun Naim (BIRCU, 2021)
The aim of this study is to explain the implementation of aspects in the inclusive education curriculum and character building that leads to the development of character values in primary education. Education is held as a part of fulfilling the rights of every child to develop their academic potential and non-academic potential. In order to reach the goal, every child has a right to get a good education, including children with special needed. This study is a descriptive qualitative study. The data was obtained from the learning description in the design development of inclusive curriculum and characters that are integrated in the curriculum. The techniques used to collect the data are literature review and interview with the teacher of schools that uses inclusive curriculum program in Kurikulum Tingkat Satuan Pendidikan (KTSP). The discussion is obtained from the study result of the character development implementation in the inclusive curriculum description at school, especially in Al Azhaar Islamic Elementary School and Noble National Academy Elementary School.